Fabrication of New Fe3O4/PVA/(C6H7O6Na)n Nanohybrid Ferrogels for Antibacterial Applications - Taufiq,Ahmad (2021)
New Fe3O4/polyvinyl alcohol (PVA)/sodium alginate (C6H7O6Na)n nanohybrid ferrogels for antibacterial applications were fabricated. The crystal and molecular structures along with optical and magnetic properties of the prepared samples were characterized. The antibacterial activity of the ferrogels against Bacillus subtilis and Escherichia coli was investigated using the agar dilution method. X-ray diffraction analysis showed that the Fe3O4/PVA comprised a PVA amorphous phase and a spinel-structured Fe3O4 crystalline phase. The Fe3O4/PVA crystallite size was 7.5–9.9 nm and the scanning electron micrographs showed that the Fe3O4/PVA agglomerated. The ferrogels were superparamagnetic with saturation magnetizations from 14.8 × 10−3 to 82.1 × 10−3 emu/g. The absorption of the ferrogels showed a bathochromic effect, accompanied by an increase in the bandgap from 2.09 to 2.18 eV with increasing Fe3O4 content in the ferrogels. The ferrogels demonstrated new potency as antibacterial agents against B. subtilis and E. coli, where their antibacterial performance increased with increasing Fe3O4 content.